2021
DOI: 10.3390/diagnostics11122266
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Echocardiographic Assessments Reveal Septal E/e’ Ratio as Independent Predictor of Intradialytic Hypotension in Maintenance for Hemodialysis Patients with Preserved Ejection Fraction

Abstract: Background: Intradialytic hypotension (IDH) is a frequent and grave complication of hemodialysis (HD). However, the dynamic hemodynamic changes and cardiac performances during each dialytic session have been rarely explored in patients having IDH. Methods: Seventy-six HD patients (IDH = 40, controls = 36) were enrolled. Echocardiography examinations were performed in all patients at the pre-HD, during-HD and post-HD phases of a single HD session. A two-way analysis of variance was applied to compare difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…On the other hand, IDH is one of the common complications of hemodialysis and is associated with all-cause and cardiovascular mortality and hospitalization odds [ 33 ]. Previous studies revealed that changes in the septal E/e’ ratio correlated with increased LV filling pressure and were the major contributing factors to IDH [ 34 ]. Taking the correlation of TAPSE/PASP and E/e’ into consideration, improving RV function may decrease the risk of IDH as well.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, IDH is one of the common complications of hemodialysis and is associated with all-cause and cardiovascular mortality and hospitalization odds [ 33 ]. Previous studies revealed that changes in the septal E/e’ ratio correlated with increased LV filling pressure and were the major contributing factors to IDH [ 34 ]. Taking the correlation of TAPSE/PASP and E/e’ into consideration, improving RV function may decrease the risk of IDH as well.…”
Section: Discussionmentioning
confidence: 99%